2003
DOI: 10.1143/jjap.42.l680
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption Behavior of AlF3Formed on Al2O3

Abstract: Thermal desorption behaviors of the AlF 3 layer formed on Al 2 O 3 in the sample temperature range from T s ¼ 300 to 930 K have been studied using molecular beam mass spectrometry combined with a time-of-flight (TOF) technique. Fluorine atoms were detected as the desorbed species at sample temperatures of T s ¼ 625 to 850 K and the intensity was found to be peaked at T s ¼ 750 K. AlF 2 species whose translational temperature T tr is approximately 100 K lower than T s were also detected as desorbed species abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…At the higher temperatures, enhanced interface and surface roughness is induced (TEM, AFM), possibly by etch reactions by F at the surface, a by-product of the WF 6 chemisorption reaction. 28 The higher temperature could induce more nucleation events, with crystal growth in more random directions as a result of the higher surface roughness. Scharf et al described a similar temperature dependent orientation of the WS 2 crystals for the WS 2 ALD from WF 6 /H 2 S in combination with diethylzinc.…”
mentioning
confidence: 99%
“…At the higher temperatures, enhanced interface and surface roughness is induced (TEM, AFM), possibly by etch reactions by F at the surface, a by-product of the WF 6 chemisorption reaction. 28 The higher temperature could induce more nucleation events, with crystal growth in more random directions as a result of the higher surface roughness. Scharf et al described a similar temperature dependent orientation of the WS 2 crystals for the WS 2 ALD from WF 6 /H 2 S in combination with diethylzinc.…”
mentioning
confidence: 99%
“…͑5͒, as tabulated in Table III. 33 F atoms were detected as the desorbed species at sample temperatures of T s = 625-850 K and their intensities were found to peak at T s = 750 K. AlF 2 species were identified as desorbed species above T s = 850 K. We have concluded that AlF 3 is reduced to subfluoride, AlF x ͑x = 1 and/or 2͒, and AlF 2 is the species desorbed from the reduced AlF x ͑x = 1 and/or 2͒ layer via a sublimation process. Although not shown in Table III, the vapor pressures of the AlF 3 dimer, i.e., Al 2 F 6 , are about two orders of magnitude smaller than those of the monomer.…”
Section: A Desorption Behavior Of Alf 3 Speciesmentioning
confidence: 99%
“…The vapor pressures of AlF 3 have been presented over the temperature range from 1238°C͑1 Torr͒ to 1537°C͑760 Torr͒ 18,19 and are thus believed to be very low at temperatures below 900 K. If the vapor pressure of AlF 3 were very low, AlF 3 would not be desorbed from the surface. 16 Thus, thermodynamics of the vapor pressure of AlF 3 is discussed. There is some discrepancy among the vapor pressures listed by Stull 18 and the NIST Standard Reference Database 19 and our results.…”
Section: Introductionmentioning
confidence: 99%